Manual ke Digital: Revitalisasi Pelayanan Publik di Kelurahan Sungai Pakning - Al Aminuddin; Sukamto Sukamto; Ibnu Daqiqil; Tisha Melia; Sonya Meitarice; Rahmat Hidayat (Indonesian Journal Publisher, 2025)
Sungai Pakning Village Office has 12 village officials who are tasked with providing services to the people of Sungai Pakning Village, Bengkalis Regency. Public services carried out by the Sungai Pakning Village Government are currently still manual. The Sungai Pakning Village assistance office has not utilized information and communication technology in providing services to the community. The absence of the application of information and communication technology is a weakness that must be addressed by the Sungai Pakning Village Government. The purpose of this community service activity is to digitize village administration services carried out in Sungai Pakning Village using OpenSID which is developed openly (open source) by the Opendesa Community. This activity begins with a location survey, problem identification, implementation, socialization, and ends with an evaluation. This community service activity produces a website that can be used by the Sungai Pakning Village Apparatus in providing digital-based services to the community. The survey results produced socialization activities related to the suitability of the website, namely 37% very appropriate/clear, 60% appropriate/clear, 2% hesitant, and 1% quite appropriate/clear. This shows that participants can accept the community service activities that have been carried out.